Pengembangan Aplikasi Investasi Syariah Pada PT Maslahat Amanah Umat Berbasis Android - Jeva Prahayusma Putra Emanda; Nurudin Santoso; Eriq Muh. Adams Jonemaro (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Day by day, the development of fintech is getting faster and make human's life easier. Even in Indonesia, fintech provider has massively proliferated. Under that reason, PT. Maslahat Ummah whose company working under the basis of sharia developed a website to make investation easier. But then, the lack of coverage for the user, and how people less prefer accessing website from their mobile phone. Because of business market that offered were mid to low class businesses. Therefore, developed an android based sharia investation application named Maslahat Kita to act as an alternative to do some finances activity through their android based mobile phone. The android based Maslahat Kita apps was created with a goal to make user feel a lot easier when it comes to transactions or contractual agreements in their businesses or investations they desire. This application also integrated real time with firebase. Therefore communication between users with specific access right is possible to be done with various devices under this application. And then, the usage of charts going to make monitoring easier for our partners. So that is why The Maslahat Kita application has gone through several testing process such as compatibility testing, integrity testing, validity testing and unit testing. Where unit testing and integrity testing used as valid indicator for the program as a whole. But in validity testing, to measure whether agreed functionality is working or not. Last but not least compatibility testing to test every versions created. We are proud to declare that the testing result should be categorized as valid, because there's no significant changes to the system's design and there is no errors at every functionality agreed, when it is being tested on different Android version.